2018
DOI: 10.5815/ijem.2018.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Vital Signs Monitoring Systems on IoT

Abstract: With the consistent development of remote sensor systems and Internet of Things (IoT) different parts of life will benefit. IoT based pervasive human services framework can possibly give blunder free restorative information and alarming system in basic conditions with constant checking. The device will minimize the need of devoted medicinal staff for patient checking and help the ailing to lead an ordinary life other than furnishing them with great restorative medical aid. This paper presents the working model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…8,9 Various studies have concluded that patients can significantly benefit from the application of remote monitoring technologies for chronic diseases, as it allows them to receive continuous treatment in their homes and stay connected with their doctors. [10][11][12][13][14] Sensor-based platforms enable monitoring of vital signs and these data can be transferred to a location where healthcare professionals can access them. The sensor-based industry, on the other hand, is growing rapidly to fulfil market needs and the market share of eHealth devices is expected to reach 201 billion dollars by 2025, with a 23% increase anticipated for the forecast period from 2019 to 2025.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Various studies have concluded that patients can significantly benefit from the application of remote monitoring technologies for chronic diseases, as it allows them to receive continuous treatment in their homes and stay connected with their doctors. [10][11][12][13][14] Sensor-based platforms enable monitoring of vital signs and these data can be transferred to a location where healthcare professionals can access them. The sensor-based industry, on the other hand, is growing rapidly to fulfil market needs and the market share of eHealth devices is expected to reach 201 billion dollars by 2025, with a 23% increase anticipated for the forecast period from 2019 to 2025.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Various studies have concluded that patients can significantly benefit from the application of remote monitoring technologies for chronic diseases, as it allows them to receive continuous treatment in their homes and stay connected with their doctors. 1014…”
Section: Introductionmentioning
confidence: 99%